2004
DOI: 10.1128/iai.72.8.4680-4688.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of theStreptococcus mutansP1 Epitope Recognized by Immunomodulatory Monoclonal Antibody 6-11A

Abstract: Monoclonal antibody (MAb) 6-11A directed against Streptococcus mutans surface adhesin P1 was shown previously to influence the mucosal immunogenicity of this organism in BALB/c mice. The specificity of anti-P1 serum immunoglobulin G (IgG) and secretory IgA antibodies and the subclass distribution of anti-P1 serum IgG antibodies were altered, and the ability of elicited serum antibodies to inhibit S. mutans adherence in vitro was in certain cases increased. MAb 6-11A is known to recognize an epitope dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 72 publications
3
30
0
Order By: Relevance
“…Elimination of this region destroyed or substantially decreased the binding of four anti-P1 MAbs that did not react with a recombinant P1 polypeptide encompassing the P region. It was subsequently shown by additive ELISA that the epitopes recognized by these MAbs were reconstituted by the interaction of discontinuous A region and P region polypeptides containing various degrees of flanking sequence (41,57). While the number of A and P region repeats within P1 homologs varies among strains and species, no Ag I/II family protein has been identified that completely lacks either of these two domains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Elimination of this region destroyed or substantially decreased the binding of four anti-P1 MAbs that did not react with a recombinant P1 polypeptide encompassing the P region. It was subsequently shown by additive ELISA that the epitopes recognized by these MAbs were reconstituted by the interaction of discontinuous A region and P region polypeptides containing various degrees of flanking sequence (41,57). While the number of A and P region repeats within P1 homologs varies among strains and species, no Ag I/II family protein has been identified that completely lacks either of these two domains.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous results that indicated that certain epitopes are masked or cryptic in the context of the complete unaltered sequence (41). MAbs 5-5D and 6-11A share the common properties of having their core epitopes reconstituted by an interaction of A and P region polypeptides, but unlike 4-10A, their binding as assessed by additive ELISA was enhanced by inclusion of sequence immediately upstream of the A region (41,57). These two MAbs again were similar to one another, and their binding improved as the number of reintroduced prolinerich repeats was increased.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…IC of HBsAg and MAbs have been reported to stimulate proliferation of immune T lymphocytes more efficiently than did antigen alone (31), and promising therapeutic efficacy of an IC vaccine in the treatment of chronic hepatitis B patients has been reported (125,130). MAbs administered as part of IC have also been demonstrated to influence the humoral immune response against the P1 surface adhesin of the dental pathogen Streptococcus mutans (18,87,99,100). Both the specificity and the isotype of anti-P1 antibodies elicited in immunized mice were altered by the MAbs.…”
Section: Immunization With Immune Complexesmentioning
confidence: 99%